Solid waste management practices of canteen concessions in a selected school in Metro Manila (2010)
The study determined the different solid waste management practices of 17 canteens in a university campus in Metro Manila. Respondents included 553 students, 112 canteen employees, 6 concessionaires, and 8 members of the University Waste Monitoring Team (UWMT). The study surveyed solid waste management practices regarding waste management education, waste generation and reduction, management of waste containers, waste separation and segregation, waste holding areas, waste storage, re-use and recovery of recyclables, and waste disposal. Results indicated a positive attitude and perception towards solid waste management among students, canteen employees, and concessionaires as well as the University Waste Management Team. Some negative attitudes were also noted such as concessionaires' preference for Styrofoam and disposable utensils, little concern by students on the maintenance of waste containers, employees' resistance to bring wastes to the garbage trucks for disposal, and the preference for open burning of wastes by both employees and concessionaires. Results of this study are expected to provide a basis for a university policy and program for an expanded solid waste management to include other business units, colleges, and administration buildings in the campus, which may also serve as a model for other schools to adopt.